Minería en pacto : implicaciones en la sociedad y la naturaleza. - Carrión Carrión, Patricia Piedad (2017)
The large scale mining activity to be implemented in the region of Pacto, it is not sustainable. This activity modifies the structure of nature and with it the ecological cycles, wildlife and directly affecting the human life. Local development projects in Pacto depends on land use which is given to the mining companies by legal mechanisms incorporated in the Estates structure. This process of eviction and dispossession generates social-environmental conflicts and the violation of human and rights of nature. The work was done through a process of scientific research with a qualitative approach, using an inductive logic method of information analysis, with bibliographical research of primary and secondary sources. It consists of three chapters: The first summarizes the theoretical framework, the main norms and public politics. That enables the large-scale mining in the country; the second addresses a brief characterization of the region of Pacto and the effects on the environment and society. The third analyzes some of the human and rights of nature which are limited or violated with the implementation of mining projects